DIGITAL PROTOCOLS IN FIXED PROSTHETICS: AN ANALYSIS OF THE VERACITY AND ACCURACY IN THE CHAIRSIDE WORKFLOW - Dutra, Ana Claudia de Souza Silva Chavinsky Zub; Cardoso, Janderson de Medeiros; Marson, Fabiano Carlos; Araujo, Fabiano de Oliveira; Milani, Paulo Augusto Pires; Cordoni, Rogério; Pupo, Fabrício Palermo; Cavalheiro, Amanda Kerin Alves; Pupo, Yasmine Mendes (Seven Editora, 2026)
Constantly evolving technologies have consolidated Dentistry as one of the most advanced sectors in the healthcare field. Digital improvements in recent years have brought significant advantages to both dentists and patients, including optimized working times, reduced costs, and increased efficiency in clinical performance. Some of the most impactful technologies introduced in the dental field are Computer-Aided Design and Computer-Aided Manufacturing (CAD/CAM) systems and intraoral scanners. Intraoral scanning technology has introduced a disruptive approach, allowing for more accurate digital analyses of dental arch components compared to traditional gypsum models. The acquired data enables the creation of three-dimensional (3D) models via 3D printing and the pre-simulation of the final treatment, resulting in faster and more accurate rehabilitations. The digital world seeks to supplant the analog workflow, tending to be the protocol of choice for patients due to greater comfort and predictability. This chapter presents the advantages of digital models for dynamic visualization and evaluation of clinical parameters of the dental arch. Through this theoretical review, we seek to analyze the effectiveness of digital scanners, assessing their trueness and precision, as well as their advantages and disadvantages for application in fixed prostheses and implant-supported restorations.